Knowledge and attitude toward evidence based practice among nurses of a tertiary care teaching hospital, Nepal (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Evidence Based Practice (EBP) raises the standard of nursing practice. The objective of this study was to assess knowledge and attitude toward EBP among nurses of Patan Hospital, Patan Academy of health Sciences (PAHS), Nepal.Methods: This was a cross-sectional study conducted from 12th August to 7th September 2018. Convenience sampling was used to select nurses with bachelor degree in nursing, working at Patan Hospital, PAHS, Nepal. Data were collected using self-administered semi-structured questionnaire to find out knowledge and attitude of nurses towards EBP.Results: Out of 125 nurses participated, 61 (48.8%) had average level of knowledge, 19 (15.2%) had good knowledge and 45 (36.0%) poor level of knowledge of EBP. Positive attitude toward EBP was found in 123 (98.4%). There was weak positive (r = 0.263) relationship between knowledge and attitude of EBP.Conclusions: Nearly half of the nurses had an average level of knowledge regarding EBP, and nearly all had positive attitude toward it.